Dryland no-till wheat seeding and fertility rates for north central Kansas - Whitney, Todd Dean (Kansas State University, 2008)
Abstract Hard red winter wheat (Triticum aestivum L.) is the predominate crop grown in North Central Kansas; and no-till wheat production practices have gained popularity in this region. No-till advantages may include: increased stored soil moisture, decreased labor costs, and increased soil conservation compared with conventional cropping systems. Seeding rates and fertility rates are two important no-till management decisions for producers. Therefore, a two-year study was conducted to determine the optimum wheat seeding and fertility rates in north central Kansas comparing the winter wheat cultivars 'Overley' and '2145'. Treatments also included seeding rates (100 kg ha-1 vs. 134 kg ha-1) and fertility rates (0, 78, 112, 146 kg ha-1). A fungicide application study was also conducted with this two-year study but proved to be statistically insignificant during the two years. Overall, the variety selection and fertility rates affected grain yields. The higher fertilizer treatments increased wheat grain yields. However, the seeding rate yield differences were not significant either year of this study. In the fungicide study, 2145 responded more to fungicide applications than Overley in 2006; but in 2005 there was no statistical advantage for a fungicide treatment with either variety. For this study, wheat varieties were planted during the recommended optimum "fly-free" seeding date period (4 October through 10 October). Although this study did not record yield differences between wheat drilled at higher or lower seeding rate during the recommended seeding period, other research does indicate that seeding rates should be increased if planting dates are extended well beyond the optimum period. Further outcomes from this study indicate that nitrogen rates should be adjusted based on field yield expectations. Although timely rainfall and/or stored soil moisture are the most limiting yield factors in dryland wheat production in north central Kansas, research results indicate that wheat yields increase with higher fertility rates when moisture is not a limiting factor. This research may be applied to north central Kansas wheat fields particularly where no-till farming practices are being used in wheat following wheat fields.
Keywords: Wheat; No-till; Agriculture, Agronomy (0285)